The Effect of Work Professionalism, Compensation, and Work Environment on Employee Performance at Goa Mesari Beach Club, Melasti, Kuta Selatan - Mulyani, Komang Dewi; Suarmanayasa, I Nengah; Suwena, Kadek Rai (SAINTIS Publishing, 2026)
This study aims to empirically demonstrate the effects of work professionalism, compensation, and the work environment on employee performance at Goa Mesari Beach Club, Melasti Kuta Selatan. The population in this study was all employees of Goa Mesari Beach Club, Melasti Kuta Selatan, totaling 42 people. Sampling was conducted using saturated sampling, meaning the entire population was used as the research sample. Data collection used a questionnaire with a 1-5 Likert scale. The data analysis technique employed multiple linear regression using IBM SPSS version 25. The results of the study indicate that partially, work professionalism, compensation, and work environment have a positive and significant effect on employee performance. Simultaneously, these three independent variables have a significant effect on employee performance at Goa Mesari Beach Club, Melasti Kuta Selatan. These findings provide practical implications for the management of Goa Mesari Beach Club, suggesting that to sustain and enhance employee performance, the organization must prioritize competitive compensation strategies and foster a supportive work environment. Furthermore, strengthening work professionalism through continuous development is essential for achieving optimal organizational outcomes in the hospitality sector.